Integrative taxonomy, whole organelle genomes and endosymbiosis in Rhopalodia sterrenburgii Krammer - Chang, Aimee Caye G.; Amaral, Mailor W. W.; Keepers, Kyle G.; Greenwood, Megan; Li, Jingchun; Hamsher, Sarah E.; Miller, Scott R.; Kociolek, J. Patrick (Frontiers in Protistology, 2025)
Despite their ecological significance and unique endosymbiotic capabilities, diatoms in the genus Rhopalodia remain poorly represented in genomic databases, particularly with respect to the availability of complete genomes from multiple organellar compartments. This study addresses that gap by presenting, for the first time, the complete chloroplast (133,086 bp), mitochondrial (36,786 bp), and spheroid body (3,024,495 bp) genomes of Rhopalodia sterrenburgii, a nitrogen-fixing diatom with a cyanobacterial endosymbiont. Phylogenetic reconstruction based on five genes from different cellular compartments (18S, 28S, rbcL, psbC, cob) placed R. sterrenburgii as a basal lineage relative to R. gibba (Rhopalodia sensu lato) and the Epithemia sensu stricto species E. argus, E. turgida, and E. sorex, providing new insights into evolutionary relationships within Rhopalodiales. Additionally, pathway analysis revealed the progressive loss of genes involved in vitamin B12 and chlorophyll a biosynthesis in more recently diverged Rhopalodia and Epithemia lineages. Our findings support a pattern of genome reduction in symbiotic diazotrophic diatoms, potentially driven by coevolution with their endosymbionts, and an increasing reliance on integrated metabolic functions between the host and the endosymbiont.